(untitled) (Economics and region, 2023)
The COVID-19 pandemic affected not only the economy, but the entire society. This led to drastic changes in the company’s activities. The article shows the problems that arise in companies as a result of the COVID-19 pandemic. Thus, the pandemic has caused many businesses to face financial problems due to mass layoffs and company closings. Overall, it affected various industrial sectors. As COVID-19 created unprecedented challenges, companies had to adapt. The article identifies possible solutions to the problems faced by enterprises. Containment of the spread of the coronavirus had important consequences for sectors of the economy, both globally and nationally. In this regard, it was necessary to accelerate the development of technologies to reduce or prevent the negative effects of COVID-19. According to the study, the pandemic forced digitalization and required companies to restructure their business models in this direction. Investments in digital technology help companies make their countries more competitive.